1987
DOI: 10.1149/1.2100636
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Optimal Conditions for the Development of Preferred Oriented Platinum Surfaces by Means of Fast Square Wave Potential Perturbations

Abstract: Changes in the voltammetric response of polycrystalline platinum in the direction expected for preferred oriented surface electrodes are achieved after applying a fast repetitive square wave potential signal covering the potential range of H-and O-electroadsorption/electrodesorption. The influence of the characteristics of the square wave potential signal on the voltammetric response of the modified platinum surfaces is systematically studied to establish the optimal conditions for obtaining surface structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 30 publications
(62 reference statements)
3
25
0
Order By: Relevance
“…The voltammogram of the electrofaceted (100)-type Pt electrodes in 1 M &So4 in the 0.06-0.7 V range ( Fig. 1) reproduces exactly the one previously reported in the literature (1)(2)(3)(4) and is also very similar to the voltammogram of a Pt(100) single crystal electrode under the same conditions (12,(17)(18)(19)(20). The roughness factor of electrofaceted (100)-type Pt electrodes was 1.1 as determined by comparing the experimental H-adatom voltammetric charge density to that of the H-adatom monolayer calculated for a Pt(100) single crystal surface (15).…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…The voltammogram of the electrofaceted (100)-type Pt electrodes in 1 M &So4 in the 0.06-0.7 V range ( Fig. 1) reproduces exactly the one previously reported in the literature (1)(2)(3)(4) and is also very similar to the voltammogram of a Pt(100) single crystal electrode under the same conditions (12,(17)(18)(19)(20). The roughness factor of electrofaceted (100)-type Pt electrodes was 1.1 as determined by comparing the experimental H-adatom voltammetric charge density to that of the H-adatom monolayer calculated for a Pt(100) single crystal surface (15).…”
Section: Methodssupporting
confidence: 88%
“…It has been recently found that the voltammetric characteristics of polycrystalline Pt can b e modified by applying fast potential cycling in acid electrolytes (1)(2)(3). Results obtained at present show that those electrodes exhibiting (100)-type preferred orientations behave in a very reproducible way and exhibit a very clear faceting (3)(4)(5). Nevertheless, the stabilized voltammetric response of these electrodes can be achieved only after they have been potential cycled under certain conditions within the potential range of bulk water stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has to be said that pc surfaces also exhibit surface restructuring, and in the case of the application of periodic potentials, they lead to the electroformation of microfacets [12]. It is well known that the application of fast potential periodic programs on platinum, rhodium, iridium, gold, or palladium produces permanent morphological changes with defined orientations, which depend on the potential limits and frequency of the routine by a microfacetting process [16][17][18]. The electrochemical responses of these stepped surfaces are similar to those of stepped crystalline surfaces [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of these potential programs are summarized in Ref. (14). On the other hand, it was recently found (20) that a potential program, consisting of a medium-frequency wave potential routine (MFWPR), applied to a Pt/aqueous acidic solution interface, produces H subsurface sites and the increase of (110) rows on the Pt surface.…”
Section: Introductionmentioning
confidence: 99%